2017
DOI: 10.1590/1678-4499.557
|View full text |Cite
|
Sign up to set email alerts
|

Statistical methods to study adaptability and stability of wheat genotypes

Abstract: The data analyzed in this study showed that the AMMI1 and GGE biplot methods are equivalent to rank genotypes for stability and adaptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
5
30
0
2
Order By: Relevance
“…Due to various factors that influence the determination of which genotype should be selected for specific growing conditions, it is necessary to employ and adapt biometric models to obtain accurate and reliable estimates that minimize distortions imposed by biases intrinsic to phenotypic measurements (Bornhofen et al, 2017). Phenotypic expression of seed yield is more than 80% due to growing environment effects.…”
Section: Introductionmentioning
confidence: 99%
“…Due to various factors that influence the determination of which genotype should be selected for specific growing conditions, it is necessary to employ and adapt biometric models to obtain accurate and reliable estimates that minimize distortions imposed by biases intrinsic to phenotypic measurements (Bornhofen et al, 2017). Phenotypic expression of seed yield is more than 80% due to growing environment effects.…”
Section: Introductionmentioning
confidence: 99%
“…Users who research the associations between stability indexes (e.g., Woyann et al, 2018; Bornhofen et al, 2017; Freiria et al, 2018; Shahbazi, 2019) often find difficulties in computing the set of statistics and binding them into a “ ready-to-read ” file. provides an efficient solution for doing that.…”
Section: The Packagementioning
confidence: 99%
“…Although useful, these packages do not offer options to perform a complete analysis of MET data, i.e., to provide tools for all steps of the analysis (check, manipulation, analysis, and visualization of data). For example, requires as input data a two-way table containing genotype by environment means with genotypes in rows and environments in columns, but doesn’t provide any function to create quickly such table from data that often is in a “ long ” format in R. In addition, several studies often compare different stability methods (e.g., Woyann et al, 2018; Scapim et al, 2010; Bornhofen et al, 2017; Freiria et al, 2018; Shahbazi, 2019; Teodoro et al, 2019). This requires a range of different packages to be used, making it the coding tedious and difficult to follow.…”
Section: Introductionmentioning
confidence: 99%
“…A frequent question of the breeder is about which method to choose. Studies have showed that some methods traditionally used for evaluating phenotypic stability are not complementary, because they are based on similar concepts of stability (Bornhofen et al 2017). Rono et al (2016) suggested that this choice can be made according to the profile and the characteristics of the data set to be analyzed.…”
Section: Introductionmentioning
confidence: 99%